Two Masters of Surgery in Parma during the Middle Ages - Cervellin, Gianfranco; Mitaritonno, Michele; Longobardi, Ugo; Virdis, Raffaele (Acta Biomedica Atenei Parmensis, 2020)
During the Middle Ages, Parma, in Northern Italy, undoubtedly represented a landmark for surgical science and practice all around Europe. Around the same period the Salernitan Medical School, already famous since the high Middle Ages, reached its whole scientific role. Due to the importance reached by the School, for centuries several physicians throughout Europe, aiming for an international fame, told they were “Salernitan”. One of the most famous examples is represented by Roger Frugardi, or Ruggero Frugardo, or Ruggero da Parma (before 1140 – about 1195), who was widely known as “Rogerius Salernitanus” (Roger of Salerno), meaning that his scientific success was a consequence of the affiliation to the Salernitan Medical School. Roger wrote an important book, the “Practica Chirurgiae” (Surgical Practice), also known as “Rogerina”, edited and published by his pupil Guido “the young” of Arezzo. It was the first Handbook of Surgery in the post-Latin Europe, containing important innovations, such as the very first description of a thyroidectomy, thus influencing surgical practice until late Renaissance. The Roger’s pupil Rolando dei Capelluti was the successor and extensor of his Master’s work. In his work he particularly developed the cranial surgery and the study of neurological diseases (e.g., epilepsy or mania). His masterwork, known as “Rolandina”, also influenced European surgery for centuries.